Experimental and smoothed particle hydrodynamics analysis of interfacial bonding between aluminum powder particles and aluminum substrate by cold spray technique - Manap, A. (2020)
This study aims on the dominant bonding mechanism between aluminum powder particles and aluminum substrate evaluated both experimentally and numerically. Aluminum particles were deposited at different velocities onto an aluminum substrate by cold spray (CS) technology. The crater, bond, and interface morphology upon impact were characterized using scanning electron microscopy, focused ion beam processing, and transmission electron microscopy. Experimental results reveal that rebound phenomenon existed at high velocities and excellent contact is obtained above the critical velocity. This denotes that ideal deposition occurs at a certain particle velocity scale. Meanwhile, the numerical analysis was performed via smoothed particle hydrodynamics (SPH) method. The simulated particle deformation behavior agreed well with the experimentally evaluated impact morphology, which confirms the viability of the SPH procedure for CS simulation. Furthermore, the numerically calculated deposition range was in correspondence with the experimental findings. The analysis demonstrates that interfacial bonding between the powder particles and substrate is influenced by the adhesive intersurface forces of the contacting surfaces. © 2019, Springer-Verlag London Ltd., part of Springer Nature.